2021
DOI: 10.1002/mrd.23541
|View full text |Cite
|
Sign up to set email alerts
|

Update about the disrupting‐effects of phthalates on the human reproductive system

Abstract: Phthalate esters are synthetic chemicals used in the plastic industry as plasticizers and consumable products. According to United Nations, about 400 million tons of plastic are produced every year. In parallel with increased production, the concerns about its effects on human health have increased because phthalates are endocrinedisrupting compounds. Humans are continuously exposed to phthalates through different routes of exposure. Experimental data have associated the phthalates exposure to adverse effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 173 publications
0
11
0
Order By: Relevance
“…Phthalates are a class of chemicals found in a wide variety of consumer products due to their plasticizing abilities (Kelley et al 2012;Net et al 2015;Zota et al 2014). Like BPA, phthalates have known endocrine disrupting properties and are considered reproductive toxicants (reviewed in Mesquita et al 2021, Seda et al 2021. In this study, out of the nine phthalates examined in yeast, none showed an effect on gametogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phthalates are a class of chemicals found in a wide variety of consumer products due to their plasticizing abilities (Kelley et al 2012;Net et al 2015;Zota et al 2014). Like BPA, phthalates have known endocrine disrupting properties and are considered reproductive toxicants (reviewed in Mesquita et al 2021, Seda et al 2021. In this study, out of the nine phthalates examined in yeast, none showed an effect on gametogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although no usage classes were linked strictly with reprotox20 toxicants in our assay, among the chemical classes we considered, bisphenol and QAC chemical structures were the strongest predictors for reproductive toxicity. Interestingly, phthalates were not found to be predictors, although this chemical category has been associated with poorer reproductive outcomes in mammals (Mesquita et al 2021;Repouskou et al 2021). We will discuss this apparent discrepancy below.…”
Section: Bisphenol and Qac Chemical Classes Were Strongest Predictors For Reproductive Toxicitymentioning
confidence: 91%
“…Triclosan has already been detected in several matrices, such as in urine, blood, serum, and breast milk ( Table 4 ). For this reason, some studies have been conducted to determine whether or not the presence of TCS can affect the foetus, through crossing the placental barrier, or even if it can induce adverse effects in future generations, as already observed for other endocrine disruptors [ 49 , 50 , 51 ].…”
Section: Metabolismmentioning
confidence: 99%
“…Exposure to EDCs, such as phytoestrogens, polycyclic aromatic hydrocarbons, flame retardants, plasticizers, pesticides, and cosmetics is an integral and fundamental part of human exposure and can occur by multiple pathways including air, food, water, and consumer products. However, this exposure led to several adverse effects on human health, including on cancer, reproductive, metabolic, and neurobiology systems, and cardiovascular disorders (e.g., coronary artery disease, hypertension, atherosclerosis, or myocardial infarction) (Zlatnik, 2016;Gore et al, 2019;Papalou et al, 2019;Fu et al, 2020;Mariana and Cairrao, 2020;Mesquita et al, 2021). Concerns about endocrine exposure have increased as the modulation of EDCs on the actions of natural hormones is discovered to involve a range of additive, synergistic, or negative biological effects (Feron et al, 2002;Fowler et al, 2012;Ribeiro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%